The Utilization of Virtual Technology Post-Pandemic in Arabic Language Learning for Postgraduate Students at UIN Maulana Malik Ibrahim Malang - Rahma Yanti, Silvia; Amelia, Ulfi; Aini, Nurul; Hilmi, Danial (Indonesian Journal of Arabic Education and Learning, 2025)
Post-Covid-19 pandemic, virtual technology is no longer merely a solution for online learning but has become an integral part of modern education. Students of the Arabic Language Education (PBA) postgraduate program at UIN Maulana Malik Ibrahim Malang frequently utilize online platforms in learning activities to support teaching and learning processes, including discussions, presentations, assignment submissions, and evaluations. This study aims to describe the utilization, advantages, and disadvantages of virtual media technology in Arabic language learning among PBA postgraduate students after the pandemic. The study employs a mixed-method approach, combining qualitative and quantitative descriptive methods. Data were collected through unstructured interviews and questionnaires distributed to PBA postgraduate students. The findings reveal that students utilize virtual technology such as video conferencing platforms like Zoom and Google Meet for interactive learning, language learning applications like Duolingo for self-directed skill improvement, and digital dictionaries for flexible material access and vocabulary comprehension. Online discussion forums like WhatsApp are also used for collaboration and information exchange. Furthermore, students experience several advantages of virtual technology in learning Arabic, including time and place flexibility, easy access to learning materials, online interaction with teachers and peers, multimedia utilization, and self-paced learning. However, students also face challenges, including poor internet connections, limited direct interaction with instructors, difficulties understanding material online, lack of motivation for independent study, and insufficient opportunities for speaking practice.